FoxP3(+) regulatory T cells essentially contribute to peripheral CD8(+) T-cell tolerance induced by steady-state dendritic cells - Schildknecht, Anita (National Academy of Sciences, 2010)
Peripheral T-cell tolerance is thought to significantly contribute to the prevention of autoimmunity, and it has been shown that antigen-presenting steady-state dendritic cells efficiently induce peripheral tolerance. We previously showed that dendritic-cell–induced tolerance is a T-cell–intrinsic process that depends on coinhibitory molecules such as programmed death-1. Here we specifically analyze the involvement of FoxP3(+) regulatory T cells, which are known to be important for maintenance of self-tolerance. We show that antigen presentation by steady-state dendritic cells failed to induce peripheral tolerance in the absence of FoxP3(+) regulatory T cells but induced protective CD8(+) T-cell–mediated immunity instead. Regulatory T-cell–depleted mice had massively increased numbers of dendritic cells in lymph nodes. Dendritic cells isolated from mice without regulatory T cells had up-regulated costimulatory molecules and showed stronger T-cell stimulatory capacity ex vivo, suggesting that regulatory T cells contribute to peripheral tolerance by keeping the dendritic cells in an immature state. Using blocking antibodies, we demonstrate that CTLA-4 but not IL-10 is necessary for control of dendritic cells by regulatory T cells.